TBI history and psychological symptom improvements following exercise therapies among U.S. service members - Walter, Kristen H.; Otis, Nicholas P.; Crocker, Laura D.; Myers, Hayley C.; Kobayashi Elliott, Kim T.; Michalewicz-Kragh, Betty (Frontiers in Human Neuroscience, 2025)
BackgroundMajor depressive disorder (MDD) is a prevalent and debilitating mental health disorder that is commonly comorbid with posttraumatic stress disorder (PTSD) and history of traumatic brain injury (TBI) in the U. S. military population. Exercise, particularly in natural environments, has been shown to effectively reduce depression and comorbid PTSD symptoms. However, little is known about whether history of TBI moderates symptom improvements following exercise interventions. Previous research has largely shown that military personnel with a history of TBI similarly benefited from evidence-based psychotherapy compared to those without a history of TBI. In contrast, no studies to date have compared those with and without a TBI history on symptom outcomes following exercise interventions.MethodsThe present study is a secondary analysis of a clinical trial evaluating surf and hike therapies among active duty service members with MDD. Depression and PTSD symptom outcomes were compared between service members with (n = 47) and without (n = 48) a TBI history to determine whether TBI history moderated treatment response.ResultsMultilevel modeling results indicated that history of TBI was not significantly related to change in depression symptoms over time (ps = 0.713–0.994). History of TBI was also not significantly associated with PTSD symptom severity from pre-to postprogram (p = 0.832); however, from preprogram through 3-month follow-up, service members without a history of TBI improved 14.7 points more than those with a TBI history (p = 0.018). Specifically, service members without a TBI history demonstrated continued improvement from postprogram to 3-month follow-up, while those with a TBI history maintained the gains achieved at postprogram. Potential explanatory factors, such as follow-up program attendance, physical activity levels, and concurrent mental health treatment, were investigated for their influence on this relationship and no significant effects emerged (ps = 0.143–0.822).ConclusionStudy findings showed that TBI history did not moderate depression outcomes, or PTSD outcomes from pre-to postprogram, following surf and hike therapies. However, service members without a history of TBI reported significantly greater improvements in PTSD symptom severity during the follow-up period, whereas those with a TBI history maintained their gains. Results suggest that while comparable in the short term, TBI history may reduce longer term PTSD symptom improvements following exercise interventions, such as surf and hike therapies.